(untitled) (Global Journal of Medical Research, 2026)
Facilitating successful early and sustained remission from substance use disorder remains an extraordinarily difficult puzzle for both clients and supporting persons to navigate. Ninety years since Alcoholics Anonymous developed its twelve step, spiritual approach to recovery from the devastation of alcoholism, initiating and sustaining abstinence from addictive substances remains a tremendous challenge. While the 12-step community continues to support addicted persons at no cost through meetings and relationships, psychology, counseling and medicine are continuing to develop approaches for people to achieve recovery from addiction. To date, there is minimal convergence in these approaches leaving affected individuals with often confusing choices in seeking necessary recovery support. The unfortunate result is the predominant view of substance use disorder as a chronic relapsing disorder whereby relapse is embedded as fundamental to its nature. Greater societal stressors and increasingly dangerous substance access is resulting in death by overdose becoming a major public health issue.